Bacterial cellulose / melanin composite material as well as preparation method and application thereof
The microbial fermentation method synthesizes bacterial cellulose/melanin composite material, which solves the problem of poor adsorption performance and tedious process of modified bacterial cellulose, and achieves more efficient heavy metal adsorption and ultraviolet absorption performance.
Patent Information
- Application Number
- CN202411382994.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
AI Technical Summary
The existing modified bacterial cellulose has shortcomings in the adsorption performance of heavy metals, and the modification process is complicated.
Bacterial cellulose/melanin composite materials are synthesized in situ through microbial fermentation, and melanin is embedded in the bacterial cellulose network to enhance adsorption performance.
The bacterial cellulose/melanin composite material has achieved significant improvements in heavy metal ion adsorption and ultraviolet absorption, while simplifying the preparation process and reducing costs.
Smart Images

Figure CN119351495A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biochemical engineering, and specifically relates to a bacterial cellulose / melanin composite material and a preparation method and application thereof. Background Art
[0002] In recent years, due to the increasingly serious environmental problems caused by petrochemical products, people's environmental awareness has also been increasing. Researchers are working hard to design and produce biodegradable polymers and composite materials. These materials are mainly derived from plants, microorganisms or organic waste, such as lignin, starch, cellulose, etc. These biodegradable polymers and composite materials can be decomposed into harmless substances by microorganisms under appropriate conditions, thereby reducing pollution to the environment.
[0003] Bacterial cellulose (BC), as a biodegradable polymer, has good application prospects in the field of heavy metal treatment due to its good water holding capacity, large specific surface area, and the presence of a large number of hydroxyl groups. However, since pure bacterial cellulose has limited adsorption capacity for heavy metals, enhancing the adsorption capacity of bacterial cellulose is the main goal of current research.
[0004] At present, some researchers use physical or chemical modification methods to modify bacterial cellulose in order to increase the specific surface area of bacterial cellulose, thereby increasing the adsorption capacity of the modified bacterial cellulose. However, the existing modified bacterial cellulose has problems such as poor adsorption performance and complicated modification process. Summary of the invention
[0005] The purpose of the present invention is to provide a bacterial cellulose / melanin composite material and a preparation method and application thereof, so as to solve the problems of poor adsorption performance and complicated modification process of the existing modified bacterial cellulose.
[0006] In a first aspect, the present invention provides a method for preparing a bacterial cellulose / melanin composite material, comprising the following steps: S1, inoculating a bacterial cellulose-producing strain into a first culture medium for static culture, and obtaining bacterial cellulose through separation; S2, adding a second culture medium to the bacterial cellulose for fermentation culture, and obtaining a bacterial cellulose / melanin composite material through separation; wherein, in step S2, the second culture medium contains a bacterial cellulose-producing strain.
[0007] In the present invention, the inventors have found that the bacterial cellulose / melanin composite material can be synthesized in situ more simply and efficiently by biological methods, and the prepared bacterial cellulose / melanin composite material has good heavy metal ion adsorption performance and good ultraviolet absorption performance. Therefore, it has good application prospects in heavy metal adsorption and ultraviolet absorption.
[0008] In some embodiments, in step S1, the bacterial cellulose producing strain inoculated is Gluconacetobacter xylinus (ATCC700178), and the inoculation amount of the strain is 0.5-2% (V / V), for example, 0.5%, 1%, 1.5%, 2% or other values within this range.
[0009] In some preferred embodiments, the inoculation amount of the bacterial strain is 1% (V / V).
[0010] In some embodiments, in step S1, the first culture solution includes the following components: fructose 15-25 g / L (for example, 15 g / L, 17 g / L, 20 g / L, 23 g / L, 25 g / L or other values within the range), yeast extract 5-15 g / L (for example, 5 g / L, 7 g / L, 10 g / L, 13 g / L, 15 g / L or other values within the range), peptone 3-7 g / L (for example, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L or other values within the range), dipotassium hydrogen phosphate 1-5 g / L (for example, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L or other values within the range), and the pH value of the culture solution is 4-6, for example, 4, 4.5, 5, 5.5, 6 or other values within the range.
[0011] In some preferred embodiments, the first culture solution comprises the following components: 20 g / L fructose, 10 g / L yeast extract, 5 g / L peptone, 3 g / L dipotassium hydrogen phosphate, and the pH value of the culture solution is 5.
[0012] In some embodiments, in step S1, the static culture step specifically includes: culturing for 5-9 days, for example, 5 days, 6 days, 7 days, 8 days, 9 days or other values within the range, at a temperature of 25-35°C (for example, 25°C, 27°C, 30°C, 33°C, 35°C or other values within the range).
[0013] In some embodiments, in step S2, the bacterial strain producing melanin is Escherichia coli (BW25113 pWU59), and the inoculation amount of the bacterial strain is 0.5-2% (V / V).
[0014] In some preferred embodiments, the inoculation amount of the bacterial strain is 1% (V / V).
[0015] In some embodiments, in step S2, the second culture medium includes the following components: 80-90 g / L of disodium hydrogen phosphate dodecahydrate (for example, 80 g / L, 83 g / L, 85 g / L, 88 g / L, 90 g / L or other values within the range), 2-3 g / L of sodium chloride (for example, 2 g / L, 2.3 g / L, 2.5 g / L, 2.8 g / L, 3 g / L or other values within the range), 10-20 g / L of potassium dihydrogen phosphate L (for example, 10 g / L, 13 g / L, 15 g / L, 18 g / L, 20 g / L or other values within the range), ammonium chloride 3-7 g / L (for example, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L or other values within the range), D-glucose 2-6 g / L (for example, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L or other values within the range), magnesium sulfate heptahydrate 0.3 -0.6 g / L (for example, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L or other values within this range), calcium chloride 10-20 mg / L (for example, 10 mg / L, 13 mg / L, 15 mg / L, 18 mg / L, 20 mg / L or other values within this range), copper sulfate pentahydrate 0.02-0.06 g / L (for example, 0.02 g / L, 0.03 g / L, 0.04 g / L / L, 0.05g / L, 0.06g / L or other values within this range), isopropyl β-D-thiogalactoside 0.1-0.4mg / L (for example, 0.1mg / L, 0.2mg / L, 0.3mg / L, 0.4mg / L or other values within this range), tyrosine 0.3-0.6g / L (for example, 0.3g / L, 0.4g / L, 0.5g / L, 0.6g / L or other values within this range).
[0016] In some preferred embodiments, the second culture medium includes the following components: 85.6 g / L disodium hydrogen phosphate dodecahydrate, 2.5 g / L sodium chloride, 15 g / L potassium dihydrogen phosphate, 5 g / L ammonium chloride, 4 g / L D-glucose, 0.493 g / L magnesium sulfate heptahydrate, 15 mg / L calcium chloride, 0.04 g / L copper sulfate pentahydrate, 0.238 mg / L isopropyl β-D-thiogalactoside, and 0.45 g / L tyrosine.
[0017] In some embodiments, in step S2, the fermentation culture step specifically includes: culturing for 5-9 days, for example, 5 days, 6 days, 7 days, 8 days, 9 days or other values within the range, at a temperature of 25-35°C (for example, 25°C, 27°C, 30°C, 33°C, 35°C or other values within the range) and a rotation speed of 180-220 r / min (for example, 180 r / min, 190 r / min, 200 r / min, 210 r / min, 220 r / min or other values within the range).
[0018] In some embodiments, step S2 further includes a step of purifying the separated bacterial cellulose / melanin composite material; the purification specifically includes: washing, heating in a water bath and freeze-drying the bacterial cellulose / melanin composite material to obtain a purified bacterial cellulose / melanin composite material.
[0019] In some preferred embodiments, the water bath heating treatment is performed at a temperature of 80-120° C. for a time of 0.5-2 h.
[0020] In the present invention, the residual culture medium components and bacterial cells in the bacterial cellulose / melanin composite material can be removed by water bath heating treatment, thereby obtaining a bacterial cellulose / melanin composite material with higher purity.
[0021] In a second aspect, the present invention provides a bacterial cellulose / melanin composite material prepared by any of the above-mentioned preparation methods.
[0022] In the present invention, the structure of the material is characterized by SEM, and it is found that melanin is embedded in the network of bacterial cellulose and is compounded with the bacterial cellulose network, thereby making the bacterial cellulose / melanin composite material denser and further enhancing the adsorption performance of the bacterial cellulose / melanin composite material.
[0023] In some embodiments, the specific surface area of the bacterial cellulose / melanin composite material is 18-22 m 2 / g, pore volume is 0.13-0.15cm 3 / g, and the average pore size is 14-16nm.
[0024] In a third aspect, the present invention provides the use of the bacterial cellulose / melanin composite material as described above in heavy metal adsorption and / or ultraviolet absorption.
[0025] In some embodiments, heavy metals include Pb 2+ .
[0026] In some preferred embodiments, the bacterial cellulose / melanin composite material adsorbs Pb 2+The conditions include the following: the concentration of bacterial cellulose / melanin composite material added is 2.5-7.5g / L, containing Pb 2+ The pH value of the solution is 4-6, Pb 2+ The ion concentration is 400-1000 mg / L, the adsorption time is 50-120 min, and the temperature is 25-40°C.
[0027] In some more preferred embodiments, the bacterial cellulose / melanin composite material adsorbs Pb 2+ The optimal conditions include the following: the concentration of bacterial cellulose / melanin composite material added is 5g / L, containing Pb 2+ The pH value of the solution is 5, Pb 2+ The ion concentration was 1000 mg / L, the adsorption time was 120 min, and the temperature was 25 °C.
[0028] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention can synthesize bacterial cellulose / melanin composite materials in situ more simply and efficiently by using a microbial fermentation method, and the prepared bacterial cellulose / melanin composite materials have good heavy metal ion adsorption performance and good ultraviolet absorption performance. In addition, the preparation method of the present invention has mild conditions, is environmentally friendly, can save costs, and has good economic benefits. Therefore, it has good application prospects in heavy metal adsorption and ultraviolet absorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The SEM and physical images of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention, wherein (a) is a SEM image of the bacterial cellulose / melanin composite material at 5 μm, (b) is a SEM image of the bacterial cellulose / melanin composite material at 10 μm, (c) is a physical image of the bacterial cellulose / melanin composite material obtained when the bacterial cellulose and Escherichia coli are co-cultured for 0 days; (d) is a physical image of the bacterial cellulose / melanin composite material obtained when the bacterial cellulose and Escherichia coli are co-cultured for 3 days; (e) is a physical image of the bacterial cellulose / melanin composite material obtained when the bacterial cellulose and Escherichia coli are co-cultured for 5 days; (f) is a physical image of the bacterial cellulose / melanin composite material obtained when the bacterial cellulose and Escherichia coli are co-cultured for 7 days; Figure 2 This is an infrared spectrum of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention; Figure 3 This is a thermogravimetric curve of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention; Figure 4 This is the Zeta potential diagram of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention; Figure 5A This is an adsorption-desorption curve diagram of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention; Figure 5B This is a pore size distribution diagram of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention; Figure 6 The amount of the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention added to Pb 2+ Results graph of adsorption effect; Figure 7 The adsorption of Pb by the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention is affected by pH 2+ Result graph of the effect; Figure 8 The adsorption time of Pb by the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention is 2+ Result graph of the effect; Fig. 9 is the adsorption temperature and Pb 2+ Effect of ion concentration on the adsorption of Pb by the bacterial cellulose / melanin composite material prepared in Example 1 of the present invention 2+ Result graph of the effect; Fig.10 The bacterial cellulose / melanin composite material prepared in Example 1 of the present invention was desorbed / adsorbed three times to remove Pb 2+ Adsorption rate results graph. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.
[0032] In the present invention, Gluconacetobacter xylinum (ATCC700178) was purchased from China Institute of Biotechnology; Escherichia coli (BW25113 pWU59) was purchased from DSMZ (German Collection of Microorganisms and Cell Culture, Braunschweing, Germany).
[0033] In the present invention, the formula of the culture medium (culture solution) used is as follows: The formula of HS medium is: D-glucose 50g / L, tryptone 5g / L, yeast extract 5g / L, citric acid 1g / L, potassium dihydrogen phosphate 1g / L, disodium hydrogen phosphate 2g / L, after the initial pH value is adjusted to 5.0, sterilize at 121℃ for 20min; The formula of the first culture medium (fructose medium) is: fructose 20g / L, yeast extract 10g / L, peptone 5g / L, dipotassium hydrogen phosphate 3g / L, after adjusting the pH to 5.0 with acetic acid, it is also sterilized at 121°C for 20min; The formula of E. coli recovery medium (LB medium) is: LB broth 25g / L, sterilized at 121℃ for 20min; The formula of the second culture medium (M9 medium) is: 85.6 g / L disodium hydrogen phosphate dodecahydrate, 2.5 g / L sodium chloride, 15 g / L potassium dihydrogen phosphate, 5 g / L ammonium chloride, 4 g / L D-glucose, 0.493 g / L magnesium sulfate heptahydrate, 15 mg / L calcium chloride, 0.04 g / L copper sulfate pentahydrate, 0.238 mg / L isopropyl β-D-thiogalactoside, 0.45 g / L tyrosine, sterilized at 121°C for 20 min, of which D-glucose is sterilized alone.
[0034] Example 1 A method for preparing a bacterial cellulose / melanin composite material (BC / M), comprising the following steps: S1. Add 5 mL of HS culture medium to a sterile test tube, use an inoculation loop to take a small amount of frozen xylose acetobacter (ATCC700178) and inoculate it into the test tube, place it in a 30°C incubator and culture it at a speed of 200 r / min for 24 hours, then take 0.75 mL of the bacterial solution and inoculate it into a conical flask containing 75 mL of HS culture medium, place it in a 30°C incubator and expand it at a speed of 200 r / min for 24 hours, after the expansion culture is completed, take 0.75 mL of the above-mentioned expanded cultured bacterial solution and inoculate it into a conical flask containing 75 mL of the first culture medium and culture it statically for 7 days, remove the excess culture medium in the conical flask, and obtain bacterial cellulose; S2, add 5mL of Escherichia coli recovery medium to a sterile test tube, add 5μL of Amp and mix evenly, use an inoculation loop to take a small amount of frozen Escherichia coli (BW25113 pWU59) and inoculate it into the test tube, place it in a 30°C incubator and culture it at a speed of 200rpm for 24h, then add 75mL of the second culture solution and 0.75mL of the above-cultured Escherichia coli culture solution to the conical flask containing bacterial cellulose in step S1, culture it at a temperature of 30°C and a speed of 200r / min for 7d, and obtain a bacterial cellulose / melanin composite material after separation; S3. Rinse the bacterial cellulose / melanin composite material obtained in step S2 with distilled water for multiple times, soak it in distilled water, and heat it in a water bath at 100°C for 1 hour to remove the components and bacterial cells in the culture medium; then, soak the cellulose membrane in deionized water and repeatedly rinse its surface until it is neutral; after rinsing, freeze-dry the composite material membrane to obtain a purified bacterial cellulose / melanin composite material.
[0035] The bacterial cellulose / melanin composite material prepared in Example 1 was subjected to SEM observation, infrared spectrum analysis, thermogravimetric analysis, Zeta potential test and nitrogen adsorption-desorption test. The results are as follows: Figure 1 -5.
[0036] from Figure 1 As can be seen from (a)-1(b), in the BC / M composite material, the melanin monomer is compounded with the bacterial cellulose network in an embedded manner. Due to the successful compounding of melanin, the fiber network is more dense to a certain extent ( Figure 1 (a) and 1(b)); further, from Figure 1 It can be seen from (c)-1(f) that as the co-culture time increases, the blackness of the material surface becomes significantly darker.
[0037] from Figure 2 As can be seen from the infrared spectrum of bacterial cellulose (BC), 1070 cm -1 The absorption peak at 2900cm is caused by the stretching vibration of COH and COC on the cellulose chain. -1 The absorption peak at 3410cm corresponds to the stretching vibration of aliphatic CH. -1 The absorption peak at 1230cm corresponds to the stretching vibration of hydroxyl groups, which is the characteristic peak of bacterial cellulose. -1 The absorption peak at 1640cm corresponds to the stretching vibration of aliphatic CO. -1The absorption peak at corresponds to the stretching vibration of the C=O group, which may be caused by functional groups such as ketone, aldehyde or carboxylic acid in melanin; in the BC / M composite material, relevant characteristic peaks of BC and Melanin appear, which proves that the BC / M composite material was successfully synthesized.
[0038] from Figure 3 It can be seen that the TG curve of BC shows that from room temperature to 200℃, BC gradually changes with a certain mass loss. When the temperature approaches 300℃, the pyrolysis process of BC becomes particularly intense, with a mass loss of 60%. Finally, about 26% of carbonaceous substances remain. The TG curve of melanin shows that mass loss begins to occur at 100℃. In the temperature range of 200℃ to 400℃, the mass loss rate of melanin accelerates, decreasing by about 35%. Finally, about 42% of carbonaceous substances remain in melanin. The TG curve of BC / M composite material shows a similar starting mass change temperature to pure melanin. At first, the mass loss of the composite material is about 8%. However, at 300℃, the composite material has a significant mass loss of 50%, which is mainly attributed to the pyrolysis characteristics of BC in the composite material. Finally, about 17% of carbonaceous substances remain in the composite material. The above results show that the performance of BC / M composite material combines the relevant thermogravimetric characteristics of BC and Melanin, further indicating the successful generation of BC / M composite material.
[0039] from Figure 4 It can be seen that the potential of the BC / M composite material is negative, with a specific value of -17.7 mV. This negative potential characteristic indicates that the BC / M composite material has excellent adsorption capacity for heavy metal cations; further comparison shows that the negative value of the potential of BC / M is between the potential range of its constituent materials BC and Melanin, that is, -11.8 mV to -41.6 mV. This result is consistent with the situation of a simple composite of the two, further indicating the successful generation of the BC / M composite material; in addition, the absolute value of the negative potential of BC / M is higher than that of pure BC, indicating that the interaction force between BC / M particles is stronger. This enhanced attraction is conducive to the mutual approach and aggregation of BC / M particles, thereby bringing better adsorption effect and stability.
[0040] from Figure 5A It can be seen that the adsorption and desorption process of BC / M composite materials and BC materials are combined with type III isotherms. Figure 5B It can be seen that the pore sizes of BC / M composite materials and BC materials are concentrated in the range of 0-50nm, and the results show that BC / M composite materials and BC materials are mesoporous materials. Further, the nitrogen adsorption and desorption related data of BC / M composite materials and BC materials are shown in Table 1 below.
[0041] Table 1 Nitrogen adsorption and desorption data of BC / M composites and BC materials
[0042] As can be seen from Table 1, the BC / M composite material has a smaller specific surface area and pore size than BC, which further indicates that Melanin in the BC / M composite material is present in the bacterial cellulose grid in an encapsulated state.
[0043] Performance Test 1 The bacterial cellulose / melanin (BC / M) composite material prepared in Example 1 was subjected to an ultraviolet absorption test, and the results are shown in Table 2 below.
[0044] Table 2 UV absorption results of bacterial cellulose / melanin composites
[0045] It can be seen from Table 2 that the UV absorption performance of BC / M composites is significantly higher than that of pure BC.
[0046] Performance Test 2 The bacterial cellulose / melanin (BC / M) composite material prepared in Example 1 was subjected to Pb 2+ Adsorption test. Specifically, standard Pb 2+ (5g / L) stock solutions were prepared from Pb(NO3)2 in volumetric flasks, and the solutions were diluted to the target concentrations with deionized water as needed. Take 100mg of bacterial cellulose powder, melanin powder, and bacterial cellulose / melanin composite powder, respectively, and add them to 20mL of lead nitrate solution with an initial concentration of 100mg / L. Use dilute nitric acid and dilute sodium hydroxide solution to adjust the pH value of the experimental solution to ensure that the pH value of the solution is stable at around 5. Subsequently, the solution was placed in a drying oven at a constant temperature of 25°C and stirred at a speed of 200r / min to ensure that the components in the solution can be evenly mixed. Take a small amount of liquid from the solution at different time points, centrifuge at a speed of 10000r / min for 5 minutes, and take the supernatant. After appropriate dilution, the Pb in the supernatant was determined by 1,10-phenanthroline spectrophotometry. 2+ The concentration of Pb 2+ The calculation method of adsorption capacity (q) and adsorption rate (R) is as follows:
[0047] in, q Refers to t Moment Material for Pb 2+ Adsorption amount (mg / g); C 0 is the initial concentration of the metal added to the adsorption system (mg / L);C t Pointing at t Heavy metal concentration in solution at the moment (mg / L); V is the volume of the adsorption experiment (mL), m is the mass (g) of adsorbent added to the system in the adsorption experiment.
[0048] Furthermore, the addition concentration of bacterial cellulose / melanin composites and the content of Pb 2+ Solution pH, Pb 2+ Effects of ion concentration, adsorption time and temperature on Pb 2+ The effect of adsorption.
[0049] Specifically, at a temperature of 30°C, pH = 5, Pb 2+ Under the conditions of ion concentration of 100 mg / L and adsorption time of 120 min, the effect of BC / M addition on the Pb 2+ The effect of adsorption, the results are as follows Figure 6 shown.
[0050] from Figure 6 It can be seen that with the increase of the amount of composite material added, the adsorption rate has increased significantly, but the unit adsorption amount of the adsorbent material has decreased. This is because with the increase of the amount of composite material added, the number of -OH and -NH increases, and for Pb 2+ The adsorption effect is enhanced, thus increasing the adsorption rate. However, due to the "oversupply" of the adsorbent, the Pb bound on the unit adsorbent is 2+ The number decreases, and thus the adsorption amount per unit adsorbent decreases. When the amount of composite material added is 5 g / L (corresponding to 20 mL of solution, the mass of added material is 100 mg), it has a good unit adsorption amount while having a high adsorption rate.
[0051] In BC / M, the dosage is 100 mg, Pb 2+ The effect of solution pH on the adsorption effect was investigated under the conditions of ion concentration of 100 mg / L, temperature of 30°C and adsorption time of 120 min. The results are as follows: Figure 7 shown.
[0052] from Figure 7 It can be seen that when the pH is low, the BC / M composite material has a 2+ The adsorption rate of Pb 2+ The adsorption rate of Pb / C increased gradually because the increase of pH value made -OH and -NH in the composite material BC / M more easily to bind with Pb / C. 2+ Combined to increase Pb 2+At the same time, it can be seen from the figure that as the pH increases, the slope of the pH adsorption graph decreases. This is because as the pH increases, when the pH is too high, the Pb 2+ When Ksp was hydrolyzed, the amount of adsorption decreased due to the precipitation of lead hydroxide in the solution, so the optimal adsorption pH for BC / M was determined to be 5.
[0053] When the amount of BC / M added was 100 mg, the temperature was 30°C, pH = 5, Pb 2+ Under the condition of ion concentration of 100 mg / L, the adsorption time of composite material Pb 2+ The effect of adsorption, the results are as follows Figure 8 shown.
[0054] from Figure 8 It can be seen that with the increase of adsorption time, the BC / M composite material has a 2+ The adsorption rate of Pb increases. At the same time, the adsorption effect is obvious before 30 minutes, and the adsorption rate increases rapidly. After 30 minutes, the adsorption rate changes little. This is because with the increase of time, the composite material 2+ The adsorption is getting closer to the equilibrium state, which slows down the adsorption rate. When the time reaches a certain level, the adsorption equilibrium state is reached, and the adsorption rate tends to be stable.
[0055] Under the conditions of BC / M addition of 100 mg, pH = 5, and adsorption time of 120 min, the adsorption temperature and Pb 2+ Ion concentration for composite Pb 2+ The effect of adsorption, the results are as follows Fig. 9 shown.
[0056] from Fig. 9 It can be seen that at the same temperature, with the increase of initial concentration, the adsorption amount of BC / M composite material also increases. This is because the increase of initial concentration means that the free Pb in the solution 2+ The increase in the number of -OH and -NH groups makes it easier for them to react with Pb 2+ In addition, at the same Pb 2+ Under the condition of initial concentration, the adsorption capacity gradually decreased with the increase of temperature. This shows that BC / M has a great influence on the adsorption of Pb 2+ The adsorption process is an exothermic process.
[0057] The above results show that the bacterial cellulose / melanin composite material can adsorb Pb 2+ The optimal conditions include the following: the concentration of bacterial cellulose / melanin composite material added is 5g / L, containing Pb 2+ The pH value of the solution is 5, Pb2+ The ion concentration was 1000 mg / L, the adsorption time was 120 min, and the temperature was 25 °C.
[0058] Finally, the recycling performance of the bacterial cellulose / melanin composite material prepared in Example 1 was tested. Specifically, under optimal conditions, the bacterial cellulose / melanin composite material was used to 2+ After adsorption, 0.1M HCl solution was used for desorption after reaching adsorption saturation, thereby releasing the loaded heavy metal ions and achieving material regeneration; then, deionized water was used to repeatedly wash to neutrality to ensure complete removal of the acid; then, the regenerated material was activated with 0.1M NaOH solution and then washed to neutrality; finally, the regenerated material was placed in a freeze dryer for 36 hours of freeze drying, and the adsorption-desorption cycle was repeated. During the analysis process, 1,10-phenanthroline spectrophotometry was also used to determine the Pb in the supernatant. 2+ The concentration of Fig.10 shown.
[0059] from Fig.10 It can be seen that after three desorption / adsorption tests, the composite material has a good 2+ The adsorption rate of melanin and BC is still very high. It can also be seen that melanin and BC can maintain a good adsorption rate during repeated desorption / adsorption. By comparing pure BC and pure Melanin, the adsorption rate and cycle effect of BC / M after three desorption / adsorption are better than those of the two pure components. The results show that the BC / M composite material has good adsorption performance in Pb 2+ It has good regeneration performance during the adsorption process.
[0060] In summary, the present invention adopts the microbial fermentation method to more simply and efficiently synthesize the bacterial cellulose / melanin composite material in situ, and the prepared bacterial cellulose / melanin composite material has good heavy metal ion adsorption performance and good ultraviolet absorption performance.
[0061] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0062] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a bacterial cellulose / melanin composite material, characterized in that: The steps include: S1, inoculating a bacterial cellulose-producing strain into a first culture solution for static culture, and obtaining bacterial cellulose through separation; S2, adding a second culture solution to the bacterial cellulose for fermentation and culturing, and obtaining a bacterial cellulose / melanin composite material through separation; Wherein, in step S2, the second culture solution contains bacteria that produce melanin.
2. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: In step S1, the bacterial cellulose producing bacteria inoculated is Gluconacetobacter xylinum, and the inoculation amount of the bacteria is 0.5-2%.
3. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: In step S1, the first culture solution includes the following components: 15-25 g / L fructose, 5-15 g / L yeast extract, 3-7 g / L peptone, 1-5 g / L dipotassium hydrogen phosphate, and the pH value of the culture solution is 4-6.
4. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: In step S1, the static culture step specifically includes: culturing for 5-9 days at a temperature of 25-35°C.
5. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: In step S2, the bacterial strain for producing melanin is Escherichia coli, and the inoculation amount of the bacterial strain is 0.5-2%.
6. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: In step S2, the second culture solution includes the following components: 80-90 g / L disodium hydrogen phosphate dodecahydrate, 2-3 g / L sodium chloride, 10-20 g / L potassium dihydrogen phosphate, 3-7 g / L ammonium chloride, 2-6 g / L D-glucose, 0.3-0.6 g / L magnesium sulfate heptahydrate, 10-20 mg / L calcium chloride, 0.02-0.06 g / L copper sulfate pentahydrate, 0.1-0.4 mg / L isopropyl β-D-thiogalactoside, and 0.3-0.6 g / L tyrosine.
7. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: In step S2, the fermentation culture step specifically includes: culturing for 5-9 days at a temperature of 25-35°C and a rotation speed of 180-220 r / min.
8. The method for preparing the bacterial cellulose / melanin composite material according to claim 1, characterized in that: Step S2 also includes the step of purifying the separated bacterial cellulose / melanin composite material; the purification specifically includes: washing, heating in a water bath and freeze-drying the bacterial cellulose / melanin composite material to obtain a purified bacterial cellulose / melanin composite material.
9. A bacterial cellulose / melanin composite material prepared by the preparation method according to any one of claims 1 to 9.
10. Use of the bacterial cellulose / melanin composite material as claimed in claim 9 in heavy metal adsorption and / or ultraviolet absorption.